A Study on the Effectiveness of Payment Service Providers with its Future Prospects: A Case Study among the users in Kathmandu Valley - Bipin Paudel; Rajesh Kaji Kayastha (International Journal of Engineering and Management Research, 2022)
This main objective of the study was to analyze the effectiveness of Payment Service Providers (PSPs) and examine the challenges to PSPs in Nepal with entrance of PSOs with Open Innovation such as Unified Payment Interface (UPI) and its future prospects among the users in Kathmandu valley (includes 3 districts: Kathmandu, Lalitpur, and Bhaktapur), Nepal. The research design was descriptive and analytical type; the research is based on mixed approach having both qualitative and quantitative data. Survey was conducted with total of 435 respondents, 405 respondents were selected using non random sampling for questionnaire. The collection of primary data were through unstructured interviews and structured questionnaire. The data was analyzed using the descriptive statistics and the regression technique. The results of statistics showed that there is rising trends and adoption of PSPs among the users in Kathmandu valley. The result of the ordinal regression analysis indicated that security concern (SC) showed a positive and insignificant influence on PSPs’ performance since estimate or coefficient value of this is 0.13 with insignificant value of (p=0.308), whereas customer service (CS), low transaction fee & Merchant Discount Rate (LTFM) and cross-border peer to peer and peer to merchant transaction (CPTM) showed a positive and significant influence on PSPs’ effectiveness having coefficient value of 0.434, 0.342 and 3.201 respectively with significant value of p=0.008, 0.004 & 0.000 respectively. However, interoperability and regulatory constraints showed a negative and insignificant influence on PSPs’ effectiveness having coefficient value of -0.206 and -0.145 respectively with insignificant value of p=0.165 and 0.241 respectively. The result of second route indicated that cross-border peer to peer and peer to merchant transaction (CPTM) which is the key feature of UPI Nepal has the highest level of influence on PSPs’ effectiveness with exponentiation of the B coefficient Exp(B) =24.548 shows UPI will set an ample challenge to the existing PSPs in Nepal. The research recommended that, PSPs need to enhance the customer service with offering low transaction and MDR. Also, diversifying their business across the border.